Online nutrition education on anemia and breakfast habits in adolescent girls - Grishella Diandra Salsabila; Listyani Hidayati; Siti Zulaekah; Muwakhidah Muwakhidah; Firmansyah Firmansyah (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2024)
The body's iron levels may become insufficient when one is not in the habit of having breakfast, potentially resulting in anemia among adolescents. Online nutrition education on anemia serves as a means to enhance knowledge and breakfast habits among adolescent girls. This study aimed to determine the effect of online nutrition education on anemia on adolescent girls’ breakfast habits. The study design was a cluster randomized trial (CRTs). The subjects were randomly assigned to the treatment group (n = 99) or the control group (n = 101). Research data were collected at SMP Negeri 5 Sukoharjo and SMP Negeri 2 Sukoharjo, which were selected through simple random sampling from March to December 2022. Online nutrition education was directed for six sessions over two weeks with a 1-month reflection. Data on breakfast habits were collected using the Food Record form and analyzed using the Mann–Whitney test. No improvement in breakfast habits was observed in either group. There was no difference in breakfast habits among adolescent girls in the treatment group, who received nutritional education about anemia, and in the control group, who did not (p=0,174). In conclusion, online nutrition education has not been sufficient to improve breakfast habits among adolescent girls.